The association between endocrine therapy use and osteoporotic fracture among post-menopausal women treated for early-stage breast cancer in Ontario, Canada. (December 2021) - Blanchette, Phillip S.; Lam, Melody; Le, Britney; Richard, Lucie; Shariff, Salimah Z.; Ouédraogo, Alexandra M.; Pritchard, Kathleen I.; Raphael, Jacques; Vandenberg, Ted; Fernandes, Ricardo; Desautels, Danielle N.; Chan, Kelvin K.W.; et al.
Abstract: Background: The use of endocrine therapy for early-stage breast cancer, particularly aromatase inhibitor therapy has been associated with an increased risk of osteoporosis and fracture in clinical trials. We sought to validate this observation in real-world practice. Methods: We used health administrative data collected from post-menopausal women (aged ≥66 years) who were diagnosed with breast cancer and started on adjuvant endocrine therapy from 2005 to 2012. Patients were classified by use of either an aromatase inhibitor or tamoxifen and followed until 2017 for a new diagnosis of an osteoporotic fracture. A multivariable analysis using a Cox proportional hazards model was adjusting for age, medical co-morbidities, medication use and duration of endocrine therapy. Results: We identified 12, 077 patients of whom 73% were treated with an aromatase inhibitor as compared to 27% with tamoxifen. Our multivariable analysis did not demonstrate any significant difference in the rate of osteoporotic fracture between patients treated with an aromatase inhibitor when compared with tamoxifen [Hazard ratio (HR) = 1.09; 95% confidence interval (CI) = 0.96–1.23, p-value = 0.18]. The 5-year rate of osteoporotic fracture for patients treated with either an aromatase inhibitor or tamoxifen was 7.5% and 6.9%, respectively. A completed sensitivity analysis did observe a decreased risk of fracture associated with tamoxifen usage over time. Conclusion: We could not detect a significant difference in the rate of osteoporotic fracture among patients treated with an aromatase inhibitor versus tamoxifen. Nonetheless, the risk with tamoxifen was numerically lower and significantly decreased when accounting for total duration of endocrine therapy. Highlights: Our real-world study investigated the osteoporotic fracture risk among early-stage post-menopausal breast cancer patients. No significant difference in fracture rates was observed among patients treated with aromatase inhibitors versus tamoxifen. The risk of osteoporotic fracture decreased with tamoxifen usage over time. Bone health should be carefully monitored and optimized among breast cancer patients recieving endocrine therapy.